I'm sure there's an easier way of solving it than the way I did, but I'm not sure what it could be. Never dealt with a problem like this before.
Anyway, I just plugged in and tested. Chose random values for a, b, c, and d, which follow the rule 0 < a < b < c < d:
a = 1
b = 2
c = 3
d = 4
![\sf ax^2+(1-a(b+c))x+abc-d)](https://tex.z-dn.net/?f=%5Csf%20ax%5E2%2B%281-a%28b%2Bc%29%29x%2Babc-d%29)
![\sf 1x^2+(1-1(2+3))x+(1)(2)(3)-(4))](https://tex.z-dn.net/?f=%5Csf%201x%5E2%2B%281-1%282%2B3%29%29x%2B%281%29%282%29%283%29-%284%29%29)
Simplify into standard form:
![\sf x^2+(1-1(5))x+6-4](https://tex.z-dn.net/?f=%5Csf%20x%5E2%2B%281-1%285%29%29x%2B6-4)
![\sf x^2+(1-5)x+2](https://tex.z-dn.net/?f=%5Csf%20x%5E2%2B%281-5%29x%2B2)
![\sf x^2-4x+2](https://tex.z-dn.net/?f=%5Csf%20x%5E2-4x%2B2)
Use the quadratic formula to solve:
![\sf x=\dfrac{-b\pm\sqrt{b^2-4ac}}{2a}](https://tex.z-dn.net/?f=%5Csf%20x%3D%5Cdfrac%7B-b%5Cpm%5Csqrt%7Bb%5E2-4ac%7D%7D%7B2a%7D)
For functions in the form of
![\sf ax^2+bx+c](https://tex.z-dn.net/?f=%5Csf%20ax%5E2%2Bbx%2Bc)
. So in this case:
a = 1
b = -4
c = 2
Plug them in:
![\sf x=\dfrac{4\pm\sqrt{(-4)^2-4(1)(2)}}{2(1)}](https://tex.z-dn.net/?f=%5Csf%20x%3D%5Cdfrac%7B4%5Cpm%5Csqrt%7B%28-4%29%5E2-4%281%29%282%29%7D%7D%7B2%281%29%7D)
Solve for 'x':
![\sf x=\dfrac{4\pm\sqrt{16-8}}{2}](https://tex.z-dn.net/?f=%5Csf%20x%3D%5Cdfrac%7B4%5Cpm%5Csqrt%7B16-8%7D%7D%7B2%7D)
![\sf x=\dfrac{4\pm\sqrt{8}}{2}](https://tex.z-dn.net/?f=%5Csf%20x%3D%5Cdfrac%7B4%5Cpm%5Csqrt%7B8%7D%7D%7B2%7D)
![\sf x\approx\dfrac{4\pm 2.83}{2}](https://tex.z-dn.net/?f=%5Csf%20x%5Capprox%5Cdfrac%7B4%5Cpm%202.83%7D%7B2%7D)
![\sf x\approx 0.59,3.41](https://tex.z-dn.net/?f=%5Csf%20x%5Capprox%200.59%2C3.41)
So the answer would be A.